Brodalumab for the Treatment of Psoriasis: A Review of Phase III Trials. Issue 2 (June 2016) - Farahnik, Benjamin; Beroukhim, Kourosh; Abrouk, Michael; Nakamura, Mio; Zhu, Tian; Singh, Rasnik; Lee, Kristina; Bhutani, Tina; Koo, John
Abstract Introduction Interleukin (IL)-17 inhibitors are the most recent class of monoclonal antibodies approved by the FDA for psoriasis treatment. Preclinical and phase II studies of brodalumab, a high-affinity IL-17 receptor monoclonal antibody, have been encouraging. Methods We conducted a literature search using the PubMed database in order to assess the efficacy and safety profile of brodalumab. The search included the following key words: "psoriasis" and "IL-17" or "brodalumab." We also reviewed citations within articles to identify relevant sources. Results At week 12, the proportion of patients attaining a 75% improvement from the baseline Psoriasis Area and Severity Index (PASI 75) was similar among the three phase III trials (AMAGINE-1, 83%; AMAGINE-2, 86%; AMAGINE-3, 85%). Brodalumab remained efficacious through 52 weeks of treatment. It maintained a satisfactory safety profile; the most frequently reported adverse events consisted of nasopharyngitis, headache, upper respiratory tract infection, and arthralgia. Conclusion Use of brodalumab revealed prompt clinical improvement and a favorable short-term safety profile in phase III trials, although further extension studies are needed to assess long-term safety. Based on the results, brodalumab appears to be a potent therapeutic option for patients with moderate-to-severe plaque-type psoriasis.